Biotransformation and oxidative stress responses in fish (Astyanax aeneus) inhabiting a Caribbean estuary contaminated with pesticide residues from agricultural runoff - Mena, Freylan (2023)
The estuarine ecosystem of Madre de Dios Lagoon (MDL), in the Caribbean Coast of Costa Rica, is exposed to contamination with pesticide residues coming from the upstream agricultural areas. Biomarkers can provide a better indication of the fitness of biota in real mixture exposure scenarios than traditional lethal dose toxicity measurements. Here, we measured biomarkers of biotransformation, oxidative stress, and neurotoxicity on Astyanax aeneus, an abundant fish species in MDL. Glutathione S-transferase activity (GST), catalase activity (CAT), lipid peroxidation (LPO), and cholinesterase activity (ChE) were measured in fish collected during seven sampling campaigns, carried out between 2016 and 2018. Pesticide residues were analyzed in surface water samples collected every time fish were sampled. Residues of 25 pesticides, including fungicides, insecticides, and herbicides, were detected. The biomarkers measured in A. aeneus varied along the sampling moments, with biotransformation and oxidative stress signals showing a coupled response throughout the assessment. Furthermore, significant correlations were established between three biomarkers (GST, LPO, and CAT) and individual pesticides, as well as between GST and LPO with groups of pesticides with shared biocide action. Among pesticides, insecticide residues had a major influence on the responses observed in fish. This work demonstrates the chronic exposure to pesticide residues in MDL and how such exposure is related to physiological responses in fish that can affect their health and potentially, the trophic networks. This early warning information should be considered to improve the protection of estuarine ecosystems in the tropics.